Imaging and Focal Therapy of Early Prostate Cancer - Polascik, Thomas J. (Current Clinical Urology,, 2017)
This text encompass an up-to-date, comprehensive review of the state-of-the-art for gland preserving therapies. Fully updated and revised, this text evaluates the scientific evidence for the evolving trend to treat intermediate risk, clinically localized prostate cancer in a focally ablative manner with novel gland-preserving, focal therapy methods. Various ablative devices such as high intensity focused ultrasound, irreversible electroporation, photodynamic therapy, cryotherapy and laser ablation, among others, is discussed in regard to their strengths and limitations as a therapeutic modality. Emphasis is placed on patient selection and outcomes utilizing both advanced imaging techniques and pathologic evaluation. Current and new approaches to image cancer foci within the prostate (multiparametric ultrasonography, multiparametric magnetic resonance image, etc) are presented along with various biopsy techniques, including robotics to map prostate cancer. Patient selection based on imaging and genomic classification, adjuvants to enhance therapy, treatment strategy, outcomes and patient centered concerns is discussed, providing an acceptable balance between cancer control and improved quality of life for patients. Written by experts in the field and lavishly illustrated with detailed line-art and photographs, Imaging and Focal Therapy of Early Prostate Cancer, Second Edition is designed as a comprehensive resource for urologists, radiation oncologists, medical oncologists, radiologists, uropathologists, molecular biologists, biomedical engineers, other clinicians -- residents, fellows, nurses and allied professionals -- and researchers with an interest in the diagnosis and novel treatment of prostate cancer. It will provide insight into the latest research and clinical applications of image-guided diagnosis and minimally invasive focal, gland-preserving treatment for prostate cancer.